A Literature Study: Behavioral Observation of the Combination of Rigid and Flexible Pavements: - - Rizky, Ajeng Meiliana; Sihombing, Atmy Verani Rouly; Sugiyanto, Martinus Agus (Journal of Green Science and Technology, 2025)
The use of longitudinally laid composite pavement is currently massively used in Indonesia as part of the 272 national road standard program. This study systematically reviews and discusses the essential characteristics of semi-rigid flexible pavement widely implemented in Indonesia by comparing the bonding conditions between concrete overlays on flexible pavement; asphalt overlays on rigid pavement; longitudinal joints between flexible-flexible pavements, rigid-rigid pavements, rigid (roadway) pavements, and flexible (shoulder) pavements; and finds the potential similarity in characteristics for longitudinal joints between rigid (shoulder) pavements and flexible (roadway) pavements. The results reveal that the stiffness of the material significantly affects the remaining service life. Furthermore, high temperatures and water immersion cause stiffness of asphalt specimens loss, potentially leading to rutting and raveling. This indicates that damages due to water and temperature significantly affect the roadway, which is a structure formed with homogeneity.  Keyword: semi-rigid flexural pavement, interface conditions, stiffness modulus, residual life prediction.